Ethnobotanical survey on breast cancer treatment in the M’sila region (Central Algeria) - Bakour, Ibtissem; Houssem, Samari; Djamel, Sarri; Dehimat, Abdelouahab; Imane, Messaadi; Asma, Mezilekh; Randa, Kara (Biodiversity: Research and Conservation, 2025)
Research on the use of traditional medicine for breast cancer (BC) treatment is widespread and plays a significant role in healthcare provision. This study aimed to identify the specific plants used in traditional medicine in the M’sila province (Algeria) for BC management. An ethnobotanical study was conducted from mid-February to April 2023. Direct interviews were held, and semi-structured questionnaires were administered to the local population. As a result we identified 18 medicinal plant species with substantial use values (UV > 0.1), belonging to 15 families, mostly the Zingiberaceae, Lamiaceae, Amaryllidaceae, and Asteraceae. The most frequently cited species included Curcuma domestica Valeton., Ephedra alata Decne, Panax ginseng C.A. Mey., Allium sativum L., Linum usitatissimum L., Zingiber officinale Roscoe, Annona muricata L., and Atriplex halimus L. Most commonly, leaves (30.2%) or all parts (20.5%) were used. The majority of the remedies were prepared in the form of decoction (39.0%) and powder (26.2%). The valuable ethnobotanical data from the M’sila region contribute to the knowledge of medicinal plants for BC treatment, and the findings may help to identify new anti-BC agents.